Protocol for translation and cross-cultural adaptation of diagnostic questionnaires for pediatric disorders of gut-brain interaction - Thaís Moreno Tomé; Ana Beatriz de Menezes Lima; Janaína Mezzonato Machado; Mariana Tschoepke Aires; Silvio da Rocha Carvalho; José Cesar da Fonseca Junqueira; Carlos Fernando Francesconi (Revista Paulista de Pediatria)
Abstract Objective: To describe the protocol used for translation and cross-cultural adaptation of the questionnaires developed by the Rome Foundation for the diagnosis of disorders of gut-brain interaction in the pediatric population. Methods: The protocol was proposed based on a narrative review of the literature on the cultural adaptation process of measurement instruments in epidemiology, analyzing its stages, and verifying its use and feasibility. The guidelines for the cross-cultural adaptation of diagnostic instruments developed by the Rome Foundation, which defines and periodically reviews diagnostic criteria, were incorporated into the protocol. Results: The proposed protocol includes: (i) preparation; (ii) forward translation; (iii) reconciliation; (iv) backward translation; (v) review of the backward translation; (vi) cognitive debriefing; (vii) final review; (viii) calculation of the item content validity index; and (ix) approval by the Rome Foundation. Conclusions: The methodological steps described in this protocol may contribute to future translations and cross-cultural adaptations of diagnostic questionnaires of disorders of gut-brain interaction and other materials from the Rome Foundation, enabling their use in epidemiological studies.